A Decade of Mighty Lipophagy: What We Know and What Facts We Need to Know?. (5th November 2021) - Khawar, Muhammad Babar; Abbasi, Muddasir Hassan; Rafiq, Mussarat; Naz, Naila; Mehmood, Rabia; Sheikh, Nadeem
Abstract : Lipids are integral cellular components that act as substrates for energy provision, signaling molecules, and essential constituents of biological membranes along with a variety of other biological functions. Despite their significance, lipid accumulation may result in lipotoxicity, impair autophagy, and lysosomal function that may lead to certain diseases and metabolic syndromes like obesity and even cell death. Therefore, these lipids are continuously recycled and redistributed by the process of selective autophagy specifically termed as lipophagy. This selective form of autophagy employs lysosomes for the maintenance of cellular lipid homeostasis. In this review, we have reviewed the current literature about how lipid droplets (LDs) are recruited towards lysosomes, cross-talk between a variety of autophagy receptors present on LD surface and lysosomes, and lipid hydrolysis by lysosomal enzymes. In addition to it, we have tried to answer most of the possible questions related to lipophagy regulation at different levels. Moreover, in the last part of this review, we have discussed some of the pathological states due to the accumulation of these LDs and their possible treatments under the light of currently available findings.